Acidity, sugar, and alcohol contents during the fermentation of Osmanthus-flavored sweet rice wine and microbial community dynamics - Ping Tian; Jiaqiong Wan; Tuo Yin; Li Liu; Hongbing Ren; Hanbing Cai; Xiaozhen Liu; Hanyao Zhang (PeerJ)
Sweet rice wine is a popular traditional Chinese rice wine widely loved by Chinese people for its high nutritional value. Osmanthus flower petals contain various nutrients and have good medicinal value. However, the dynamics of the sugar level, acidity, alcohol content, and microbial community during the fermentation of Osmanthus-flavored sweet rice wine have not been evaluated, which can lead to the unstable quality of Osmanthus flower sweet rice wine (OFSRW). In this study, the dynamic changes in sugar level, acidity, alcohol content, microbial community composition, and microbial metabolic pathways during traditional fermentation of OFSRW at four-time points—0 h (AG0), 24 h (AG24), 36 h (AG36), and 43 h (AG43)—were analyzed via direct titration, total acid assays, alcoholometry, and high-throughput macrogenomic techniques. First, we found that bacteria were the dominant microorganisms in the early stage of OFSRW fermentation (AG0), fungi were the dominant microorganisms in the middle and late stages of fermentation (AG24 and AG36), and Rhizopus was the main fungal genus throughout fermentation. Acidity and total sugars increased with fermentation time, and alcohol was not detected until the end of fermentation. Diversity analysis revealed that the dominant species at the beginning of natural fermentation was A. johnsonii, and R. delemar became the dominant species as natural fermentation progressed. Metabolic pathway analysis revealed that energy production and conversion, carbohydrate transport, amino acid transport, and metabolic pathways were the most active metabolic pathways in the fermenter. These results provide a reference basis for changes in the microbial community during the fermentation of cinnamon-flavored sweet rice wine.